2020
DOI: 10.1016/j.sjbs.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Newcastle disease virus reduces growth of cervical cancer cell by inducing apoptosis

Abstract: Although Oncolytic viruses have been regarded as a promising tool for targeted therapy of cancer, accomplishing high efficacy and specificity with this strategy is challenging. Oncolytic virotherapy is one of the novel therapeutic methods recently used for the therapy of human malignancies. Cervical cancer is on the major public health problem and the second most common cause of cancer death among females in less developed countries. The aim of this study was mainly to determine the apoptosis effect of oncolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 35 publications
5
43
0
Order By: Relevance
“…Consequently, finding novel methods for increasing the efficiency of tumor imaging and treatment is of great importance [1,2]. Recently, oncolytic virotherapy has provided a new outlook for the therapy of malignancies with promising outcomes [3,4]. Oncolytic viruses (OVs) specifically induce cancer cells death by infection of and spreading on tumor cells through different mechanisms such as direct lysis effect or adjacent cells fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, finding novel methods for increasing the efficiency of tumor imaging and treatment is of great importance [1,2]. Recently, oncolytic virotherapy has provided a new outlook for the therapy of malignancies with promising outcomes [3,4]. Oncolytic viruses (OVs) specifically induce cancer cells death by infection of and spreading on tumor cells through different mechanisms such as direct lysis effect or adjacent cells fusion.…”
Section: Introductionmentioning
confidence: 99%
“…However, statistics about the incidence of many thousands of newfangled cases diagnosed with cervical cancer and the huge number of deaths among previously diagnosed patients in 2018 clarify the inefficiency of present cervical cancer prevention and treatment methods [2]. To address the shortcomings of present therapeutic methods and along with advancements in synthetic biology, immunotherapy and oncolytic virotherapy have emerged as alternative or complementary cervical cancer treatments [3]. Regarding immunotherapy techniques, the employment of HPV vaccines, adoptive T-cell therapy, and immune checkpoint blockade have investigated [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of monotherapy with immune checkpoint blockade in clinical trials is doubtful and in some cases, the results are not satisfactory enough [8]. Besides these dissatisfactory approaches, oncolytic virotherapy with distinctive characteristics has shown promising results against cervical cancer [3]. Direct oncolysis along with the provocation of host systemic innate and adoptive immune responses introduce oncolytic virotherapy as one of the treatment methods with the most optimistic results in the treatment of human cancers [9].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo tracking of the MSCs migratory ability in the tumor microenvironment is essential for the application of stem cells for cancer immunotherapy. [26]. In addition to direct antitumor effect, oncolytic virotherapy also exerts a robust danger signal needed for overcoming tumor-induced immune suppression and subsequent stimulation of potent antitumor immunity in vivo [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that oncolytic NDV induces apoptosis in TC-1 cell line [26]. In addition, Kumar et al found that NDV mediates tumor cell killing through promoting the TNF-related apoptosis-inducing ligand (TRAIL)/TRAIL-R signaling, caspases activation, as well as apoptosis in the extrinsic pathway in HeLa cells [25].…”
Section: Oncolytic Ndv Induces Apoptosis In Vivo Modelmentioning
confidence: 99%